Rekayasa Bahan Pada Pekerjaan Pengaman Pantai - Raksi, Sunandar; Lakawa, Irwan; Sulaiman, Sulaiman; Sudardjat, Catrin; Sufrianto, Sufrianto (Sultra Civil Engineering Journal (SCiEJ), 2022)
Material Engineering is used to find alternatives or ideas that aim to produce better / lower costs than the previously planned price with functional limitations and quality of work. The purpose of this research is to analyze the cost efficiency and time effectiveness after analyzing the value engineering method. The analytical method used is material engineering on the type of activity in the coastal protection building which includes the casting and installation of buis concrete, mortar and cyclone concrete work with the substitution of mixed concrete materials in the work. The results showed that the cost efficiency after analyzing with the material engineering method was 14.15% or Rp. 274,670,356 of the Budget Plan as well as the time after analysis with the effectiveness of material engineering on the Polemo Beach Security Work, Poleang Timur District by 15% or 3 weeks ahead of the implementation schedule.